2000
DOI: 10.1002/1096-9098(200005)74:1<53::aid-jso13>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Biological prognostic factors for early stage completely resected non-small cell lung cancer

Abstract: Our data do not support a relevant prognostic role for p53, bcl-2, or Ki-67 immunohistochemical markers in non-small cell cancer. Tumor vessel invasion was an independent predictive factor of poor outcome in the group of patients without lymph node involvement. Pathological stage was confirmed as the most important independent prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 35 publications
3
25
1
4
Order By: Relevance
“…Immunohistochemistry used to reveal Ki-67 protein was not always performed with the same antibody: clone Mib-1 in the majority of the studies (Costes et al, 1995;Bohm et al, 1996;Fontanini et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Minami et al, 2002;Rigau et al, 2002), antibodies coming from a firm selling several clones but without mention of the clone used (Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Giaccone et al, 1995;Pujol et al, 1996;Mehdi et al, 1998;Soomro et al, 1998;Carbognani et al, 2002); any mention of the antibodies used (Tungekar et al, 1991;Harpole Jr et al, 1995Giatromanolaki et al, 1996a, b;D'Amico et al, 1999D'Amico et al, , 2000Carvalho et al, 2000;Pelosi et al, 2001)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry used to reveal Ki-67 protein was not always performed with the same antibody: clone Mib-1 in the majority of the studies (Costes et al, 1995;Bohm et al, 1996;Fontanini et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Minami et al, 2002;Rigau et al, 2002), antibodies coming from a firm selling several clones but without mention of the clone used (Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Giaccone et al, 1995;Pujol et al, 1996;Mehdi et al, 1998;Soomro et al, 1998;Carbognani et al, 2002); any mention of the antibodies used (Tungekar et al, 1991;Harpole Jr et al, 1995Giatromanolaki et al, 1996a, b;D'Amico et al, 1999D'Amico et al, , 2000Carvalho et al, 2000;Pelosi et al, 2001)…”
Section: Discussionmentioning
confidence: 99%
“…In total, 42 studies published between 1991 and 2002 were selected for this systematic review (Tungekar et al, 1991;Hayashi et al, 1993;Pence et al, 1993;Kawai et al, 1994;Costes et al, 1995;Giaccone et al, 1995;Harpole, Jr et al, 1995Bohm et al, 1996;Fontanini et al, 1996;Giatromanolaki et al, 1996a, b;Pujol et al, 1996;Bellotti et al, 1997;Ishida et al, 1997;Komaki et al, 1998;Mehdi et al, 1998;Soomro et al, 1998;D'Amico et al, 1999D'Amico et al, , 2000Dazzi et al, 1999;Dingemans et al, 1999Dingemans et al, , 2001Santinelli et al, 1999;Cagini et al, 2000;Carvalho et al, 2000;Demarchi et al, 2000;Hommura et al, 2000;Nguyen et al, 2000;Shiba et al, 2000Shiba et al, , 2001van de Vaart et al, 2000;Ferreira et al, 2001;Hayashi et al, 2001;Pelosi et al, 2001;Puglisi et al, 2001Puglisi et al, , 2002Ramnath et al, 2001;Tsoli et al, 2001;Carbognani et al, 2002;Minami et al, 2002;Rigau et al, 2002). Five were excluded because an identical patients cohort was used in another selected publication (references excluded/includ...…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…The association between Bcl-2 expression and prognosis in NSCLC is still unclear: some studies show improved outcome [13,[28][29][30][31][32][33][34] and others no survival advantage [35][36][37]. An association between Bcl-2 and poor prognosis should be expected because Bcl-2 inhibits apoptosis and should therefore favor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This is highlighted by the experience with p53. Of six studies that have evaluated four or more markers (including p53) simultaneously, three studies found an independent effect of p53 (6,30,51), whereas the remaining three did not (24,31,52). Second, most of these studies are limited by the large number of hypotheses tested in one group of patients, without confirmation of their findings in any validation cohorts.…”
Section: Reviewmentioning
confidence: 99%